KARAKTERISTIK ES KRIM SUSU KACANG TUNGGAK (Vigna unguiculata L.) DENGAN VARIASI JUMLAH KARAGENAN DAN WHIPPING CREAM - Yhulia Praptiningsih; . Tamtarini; Anisa Rahma (Faculty of Agricultural Technology, University of Jember, 2013)
Ice cream could be make from cowpea milk. The making of ice cream was need stabilizer, emulsifier and foaming agent. The most widely used of stabilizer was carrageenan, and the emulsifier and foaming agent was whipping cream. The purpose of this study was to determine the appropriate amount of carrageenan and whipping cream to produce the good properties and high preference of cowpea milk ice cream. The research was conducted by Randomaized Complitely Block Desain with 2 factors. The first factor was the amount of carrageenan (0,1%, 0,3%, 0,5%). The second factor was the amount of whipping cream (10%, 20%, 30%) from the volume of milk, and repeatly 3 times. The observation were the overrun, brightness (colour reader), texture (pnetrometer), melting rate and sensory properties (the preference of color, texture, flavor and overall). The good properties of ice cream produced by adding of 0,5% carrageenan and whipping cream 30%. The ice cream had overrun 51,39%; texture 42,60 mm/10s; melting rate 13,47%/15 minute; brightness 89,28; the preference score of color, texture, flavor, and overall respectively 3,84; 3,92; 3,88 and 3,96 (rather like to like).Keywords: ice cream, cowpea milk, carrageenan, whipping cream